La educación (moral y cívica) en una sociedad globalizada - Concepción Naval (Universidad de Navarra, 2018)
In general, globalisation is understood to be working as a unit, eventually, on a planetary scale, through networks of interconnections. A variety of standpoints have developed with regard to this novel phenomenon. There is no doubt that technological advances are changing our lives, the life of each one of us; that the virtual revolution - if it can be so called - is affecting us whether we like it or not: it has some costly personal consequences. What are the challenges of education in a globalised world, in the knowledge society? How can globalisation and diversity be combined? Is to globalise the same as to homogenise? How can citizenship be connected to diversity? What is or could be the role of the media and the new information and communication technologies in this process? Why is the reaction to the accelerated process of globalisation, a strengthening of the need for identity?